Studi Eksperimental Penggunaan Admixture Superplasticizer dalam Upaya Terhadap Peningkatan Kuat Tekan Beton - Muhammad Rizki Harahap; Indra Jhon Fischer (Jurnal Konstruksi, 2026)
Concrete is a composite material consisting of Portland cement, water, fine aggregate, coarse aggregate, and specific admixtures formulated in predetermined proportions to produce concrete of a quality that meets specified requirements. The use of admixtures is a common approach to improving the mechanical properties of concrete, particularly compressive strength. In this study, a superplasticizer admixture was applied to a K-175 grade concrete mix. An experimental approach was implemented through a series of tests at the materials laboratory of the Medan State Polytechnic. The study samples consisted of normal concrete and concrete with an admixture addition of 1.5% by weight of the cement. Compressive strength testing was conducted at 28 days of curing. The results showed that the normal concrete had an average compressive strength of 13.07 MPa, while the concrete with the superplasticizer admixture reached 16.13 MPa, representing an increase of approximately 23.41%. Thus, the use of the admixture was proven to increase the concrete’s compressive strength by 3.06 MPa compared to concrete without the additive.